Improving Agricultural Sector: The Role of Mudharabah Financing (Study on Sharia Financing Savings and Loans Cooperatives) - Syifa, Dewi Layyinatus; Ridlwan, Ahmad Ajib (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Abstract: This study aims to determine the role of mudharabah financing in a Financing Savings and Loan Cooperative towards improving the agricultural sector. Data collection techniques used are observation, interviews, and documentation. The study results indicate that cooperatives play a role in improving the agricultural sector with the help of the capital provided. The increase in the agricultural sector can be seen from the adequacy of capital, increased welfare, and increased labor. However, the improvement of cooperatives' welfare and other factors such as natural weather conditions play a role in improving farmers' welfare. As for the suitability of implementing mudharabah financing in cooperatives, there is still a discrepancy between the implementation and the DSN MUI fatwa No. 7 of 2000 concerning Mudharabah Financing, the capital used by cooperative members is not 100% of the cooperative. Members also do not get the opportunity to bargain about the amount of profit sharing.Abstrak: Penelitian ini bertujuan untuk mengetahui peran pembiayaan mudharabah di Koperasi Simpan Pinjam Pembiayaan terhadap peningkatan sektor pertanian. Teknik pengumpulan data yang digunakan ialah observasi, wawancara, dan dokumentasi. Hasil penelitian menyebutkan koperasi berperan dalam meningkatkan sektor pertanian dengan bantuan modal yang diberikan. Adapun peningkatan pada sektor pertanian dapat dilihat dari kecukupan modal, peningkatan kesejahteraan, serta peningkatan tenaga kerja. Akan tetapi, dalam peningkatan kesejahteraan koperasi tidak berperan secara keseluruhan dikarenakan terdapat faktor lain yang dapat mempengaruhi peningkatan kesejahteraan petani yakni kondisi cuaca alam. Sedangkan untuk kesesuaian pelaksanaan pembiayaan mudharabah pada koperasi masih terdapat ketidaksesuaian antara pelaksanaan dengan fatwa DSN MUI No 7 tahun 2000 tentang Pembiayaan Mudharabah, yakni modal yang digunakan anggota koperasi tidak 100% dari koperasi, serta anggota juga tidak mendapatkan kesempatan dalam melakukan tawar-menawar mengenai besaran bagi hasil.